Capacity Building Petani Sawit Dalam Memenuhi Administrasi Perkebunan Kelapa Sawit Berkelanjutan Di Desa Beringin Indah - Spanie, Gabriella; Aprilya, Nursani; Aulia, Tifa Widi; Annantasya, Nadia Putri; Pardede, Andhika; Hidayat, Taufik Al; Yuhandi, Fadhel Ahmed; Ramsa, Nashirah Najla; TB, Mesy Natalia; Situmorang, Simon (Unri Conference Series: Community Engagement, 2024)
Palm oil has become one of Indonesia's most important agricultural commodities, contributing significantly to the national economy. However, the sector also faces challenges related to sustainability, especially among independent smallholders. Recent research shows that the escalation of agricultural cooperatives can be an effective solution to improve the sustainability of oil palm plantation businesses for independent smallholders. The administration of sustainable oil palm plantations is an important element in realizing environmentally and socially responsible plantation practices. However, many oil palm smallholders in Beringin Indah Village still experience obstacles in fulfilling these administrative requirements.Dedication is carried out to solve this problem. This service is carried out from 15 July to 25 August 2024. This dedication aims to analyze the capacity building needs of oil palm smallholders in fulfilling sustainable plantation administration and design an appropriate capacity building program. The capacity building program designed includes training on sustainable plantation certification standards, documentation and reporting workshops, and assistance in managing plantation administration. The implementation of this program is expected to increase the capacity of farmers in fulfilling administrative requirements, thus encouraging the realization of sustainable oil palm plantation practices in Beringin Indah Village. This dedication contributes to the development of strategies to empower oil palm smallholders to support environmental sustainability and improve community welfare. The results of this dedication can be a reference for local governments, companies, and related organizations in designing capacity building programs that suit the needs of oil palm farmers.